A compendious study of device-to-device communication underlaying cellular networks. (18th February 2020) - Singh, Indrasen; Singh, Niraj Pratap
Device-to-device (D2D) communication is recognised as an emerging technology used in the cellular networks with many advantages such as peer-to-peer (P2P) services, higher spectral efficiency, enhanced throughput and higher data transmission capacity for the fourth generation (4G) and beyond cellular networks. To attain the rising demands of the cellular users, there is always a need to enhance the network transmission capacity of cellular networks. In Long-Term Evolution (LTE) and LTE-Advanced (LTE-A) networks, the study of D2D communications is being interested in academia, industry person and standardisation bodies. In near future, there will be billions of connected user equipment. The next generation networks (NGNs) that to be heterogeneous in nature and demanding higher data rates, lesser delays, enhanced system transmission capacity and better throughput with large coverage. As accessible licensed spectrum assets are limited and for the survival of mobile network operators, it is required to facilitate users as per their rising demands. This survey paper explores the detailed literature of D2D communication for cellular network including their classification based on spectrum used, comparison with other short-distance wireless communication technologies, mobile data traffic growth prediction, advantage and disadvantages, applications and the open issues with work done so far.